2015
DOI: 10.1002/we.1929
|View full text |Cite
|
Sign up to set email alerts
|

A new formulation for rotor equivalent wind speed for wind resource assessment and wind power forecasting

Abstract: The spurt of growth in the wind energy industry has led to the development of many new technologies to study this energy resource and improve the efficiency of wind turbines. One of the key factors in wind farm characterization is the prediction of power output of the wind farm that is a strong function of the turbulence in the wind speed and direction. A new formulation for calculating the expected power from a wind turbine in the presence of wind shear, turbulence, directional shear and direction fluctuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 16 publications
0
57
0
Order By: Relevance
“…The opposite trend was however found when the turbine operates in conditions closer to the rated wind speed. This concept is also supported by the equivalent power mathematics of Choukulkar et al that suggest that an increase in TI can only increase the available power if operating below rated conditions. The conventional representation of performance is with the coefficient of power defined by CP=P12ρAU3, where P is the turbine output power and A is the projected frontal area of the turbine.…”
Section: Introductionmentioning
confidence: 99%
“…The opposite trend was however found when the turbine operates in conditions closer to the rated wind speed. This concept is also supported by the equivalent power mathematics of Choukulkar et al that suggest that an increase in TI can only increase the available power if operating below rated conditions. The conventional representation of performance is with the coefficient of power defined by CP=P12ρAU3, where P is the turbine output power and A is the projected frontal area of the turbine.…”
Section: Introductionmentioning
confidence: 99%
“…Wharton and Lundquist (2012b) also found that vertical TI and turbulence kinetic energy (TKE) affect power performance and Rareshide et al (2009) found that veer affects power performance. Atmospheric stability induces deviations of power from the manufacturer power curve (MPC) (Motta et al, 2005;van den Berg, 2008;Vanderwende and Lundquist, 2012;Wharton and Lundquist, 2012b), and atmospheric variations across the rotor disk can influence power performance results (Sumner and Masson, 2006;Wagner et al, 2009;Choukulkar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Coherent Doppler lidars (CDL) are used in applications ranging from basic atmospheric boundary-layer research to model data assimilation (Riishøjgaard et al, 2004;Chai et al, 2004;Newsom and Banta, 2004a, b;Newsom et al, 2005;Weissmann and Cardinali, 2007;Pu et al, 2010) and to wind resource assessment (Pena et al, 2009;Lang and McKeogh, 2011;Koch et al, 2012;Pichugina et al, 2012;Hsuan et al, 2014;Newsom et al, 2015;Newman et al, 2016;Choukulkar et al, 2016). Within the wind energy industry, these instruments are viewed as cost-effective alternatives to instrumented towers for wind resource assessment provided the measurement uncertainties are within acceptable limits.…”
Section: Introductionmentioning
confidence: 99%